WADY WRODZONEDisturbances of pulmonary blood flow after the Fontan operation – computational analysis using finite element method - Mroczek, Tomasz; Małota, Zbigniew; Wójcik, Elżbieta; Król, Wanda; Składzień, Tomasz; Skalski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Objective : Fontan operation is the final, staged palliative treatment of all single ventricle types of congenital heart defects. The type of initial operation may affect the proper development of pulmonary arteries. The main objective of this paper is the assessment of pulmonary arteries morphology in angiographic studies preceding the Fontan operation and the preparation of a computer simulation of potential pulmonary blood flow disturbances in Fontan pathway. Material and methods : Thirty nine children (20 with hypoplastic left heart syndrome) who underwent the Fontan operation were included in the study. Based on angiographic and echocardiographic evaluation of pulmonary arteries and lateral tunnel morphology, four virtual models were developed. Computer simulation of blood flow were performed using the finite element method. Results : Abnormalities of pulmonary arteries development were found in 60% of children with hypoplastic left heart syndrome. Mainly the proximal segment of the right pulmonary artery was affected. Significant hypoplasia of the right pulmonary artery can result in unfavorable redistribution of pulmonary blond flow and additional loss of energy as high as 17%. Conclusions : Abnormal development of pulmonary arteries in children with hypoplastic left heart syndrome significantly enhances loss of energy in total cavo-pulmonary connection. Computer simulations of hemodynamics may be helpful in achieving better understanding of Fontan circulation.